Regulation of functional groups on graphene quantum dots directs selective CO2 to CH4 conversion - Tianyu Zhang (Nature Portfolio, 2021)
Electrochemical conversion of CO2 to fuels is a promising strategy to reduce the ever-increasing CO2 emission. Here, the authors developed graphene quantum dots (GQDs) catalysts to efficiently convert CO2 to CH4 and revealed the significance of electron-donating functional groups in regulating the reactivity of GQDs.